Dose escalation to hypoxic subvolumes in head and neck cancer: A randomized phase II study using dynamic [18F]FMISO PET/CT. (June 2022) - Welz, Stefan; Paulsen, Frank; Pfannenberg, Christina; Reimold, Matthias; Reischl, Gerald; Nikolaou, Konstantin; La Fougère, Christian; Alber, Markus; Belka, Claus; Zips, Daniel; Thorwarth, Daniela
Highlights: This study presents results of a randomized phase II trial on hypoxia dose escalation in head and neck cancer (HNC) Tumor hypoxia assessed with dynamic [18F]FMISO PET/CT is a negative prognostic factor in HNC treated with IMRT. Hypoxia dose escalation by dose painting radiotherapy is feasible und does not lead to unacceptable toxicity. Hypoxia dose escalation leads to a statistically non-significant improvement in local control of 25% Abstract: Background and purpose: Tumor hypoxia is a major cause of resistance to radiochemotherapy in locally advanced head-and-neck cancer (LASCCHN). We present results of a randomized phase II trial on hypoxia dose escalation (DE) in LASCCHN based on dynamic [ 18 F]FMISO (dynFMISO) positron emission tomography (PET). The purpose was to confirm the prognostic value of hypoxia PET and assess feasibility, toxicity and efficacy of hypoxia-DE. Materials and methods: Patients with LASCCHN underwent baseline dynFMISO PET/CT. Hypoxic volumes (HV) were derived from dynFMISO data. Patients with hypoxic tumors (HV > 0) were randomized into standard radiotherapy (ST: 70Gy/35fx) or dose escalation (DE: 77Gy/35fx) to the HV. Patients with non-hypoxic tumors were treated with ST. After a minimum follow-up of 2 years feasibility, acute/late toxicity and local control (LC) were analyzed. Results: The study was closed prematurely due to slow accrual. Between 2009 and 2017, 53 patients were enrolled, 39 (74%) had hypoxic tumors and were randomized into ST or DE. For non-hypoxic patients, 100% 5-year LC was observed compared to 74% in patients with hypoxic tumors (p = 0.039). The difference in 5-year LC between DE (16/19) and ST (10/17) was 25%, p = 0.150. No relevant differences related to acute and late toxicities between the groups were observed. Conclusion: This study confirmed the prognostic value of hypoxia PET in LASCCHN for LC. Outcome after hypoxia DE appears promising and may support the concept of DE. Slow accrual and premature closure may partly be due to a high complexity of the study setup which needs to be considered for future multicenter trials.